Storytelling As A Pedagogical Tool For Moral Development In Rural Children - Godara, Khushboo; Shubha Dube (Indian Journal of Extension Education, 2026)
The research carried out in 2025 examined the effectiveness of storytelling as an educational intervention for enhancing moral values among rural children. A pre-intervention-to-post-intervention assessment design was used. The sample included 60 students aged 10 to 12 years studying in rural primary schools in Bhaniyana village, Jaisalmer district, Rajasthan. The Moral Values Scale developed by Gupta and Singh (2016) was administered before and after a six-week storytelling programme. The programme consisted of twelve sessions based on culturally relevant moral stories highlighting honesty, empathy, fairness, cooperation, and responsibility. Each session included story narration followed by structured discussion and reflection activities that encouraged children to connect moral ideas with real-life experiences. The findings showed a significant increase in mean scores across all moral dimensions—lying, dishonesty, stealing, and cheating—after the intervention. Repeated measures ANOVA indicated significant effects of intervention and age, while gender differences were statistically nonsignificant. Correlation analysis revealed a positive association between age and moral value enhancement. The study suggests that story narration may function as an effective and culturally responsive strategy for moral education and could be integrated into rural extension and educational initiatives aimed at promoting value-based learning and holistic development.